2013
DOI: 10.1063/1.4838035
|View full text |Cite
|
Sign up to set email alerts
|

Giant pyroelectric coefficient determined from the frequency dependence of the pyroelectric signal generated by epitaxial Pb(Zr0.2Ti0.8)O3 layers grown on single crystal SrTiO3 substrates

Abstract: Epitaxial Pb(Zr0.2Ti0.8)O3 layers of good structural quality were grown on single crystal SrTiO3 substrates. The pyroelectric coefficient was estimated from the signal generated by the ferroelectric film working as a pyroelectric detector in the voltage mode, without pre-poling procedure. The obtained value is as high as 1.9 × 10−3 C/m2 K. The large value is attributed to the presence of 90° ferroelectric domains and to the compressive misfit strain, leading to an enhanced ferroelectric polarization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 35 publications
1
10
1
Order By: Relevance
“…This result suggests to us that domain walls are pinned at all frequencies. Recently, Botea et al [34] reported a pyroelectric coefficient (∼1.9 × 10 −3 Cm −2 K −1 , about 10 times higher that our measured values) of PZT epitaxial layers grown on STO substrates. The 90°ferroelectric domains and the compressive misfit strain are suggested to be causes for this giant value.…”
Section: Resultscontrasting
confidence: 52%
“…This result suggests to us that domain walls are pinned at all frequencies. Recently, Botea et al [34] reported a pyroelectric coefficient (∼1.9 × 10 −3 Cm −2 K −1 , about 10 times higher that our measured values) of PZT epitaxial layers grown on STO substrates. The 90°ferroelectric domains and the compressive misfit strain are suggested to be causes for this giant value.…”
Section: Resultscontrasting
confidence: 52%
“…For the 600 nm thick AlN layer the value of T is slightly lower, of 193 s. Therefore, the situation (ω T ) 2 1 is fulfilled. For the frequency range where (ω e ) 2 1 ( e is the electrical time constant, given by the product RC with R resistance and C capacitance of the pyroelectric element) the signal should be frequency independent and given by [31,34]:…”
Section: Discussionmentioning
confidence: 99%
“…The estimations will be made using the same procedure as in Ref. [31], thus including the effect of the substrate in the thermal time constant of the AlN layer. The quantities relevant for calculations are: density, specific heat and thermal conductivity.…”
Section: Discussionmentioning
confidence: 99%
“…Direct and indirect methods have been carefully compared, and although they can provide similar values for bulk materials, the results often significantly differ for clamped thin films 148,149 . However, several new (or at least refined) measurement techniques for pyroelectric and electrocaloric effects have been reported in the past few years and will probably lead to new discoveries [149][150][151][152][153] .…”
Section: Thermal-based Applicationsmentioning
confidence: 99%